PROGRAM PENGEMBANGAN MODEL KAMPUNG CERDAS UNTUK MENINGKATKAN MOTIVASI PENDIDIKAN MASYARAKAT DESA TANJUNG REJO, KECAMATAN PERCUT SEI TUAN, KABUPATEN DELI SERDANG, PROVINSI SUMATERA UTARA - Sondang Purnamasari Pakpahan; Yusrafiddin; Haholongan Simanjuntak; Syahril (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2023)
The development program of Smart Village to improve the education motivation of community was carried out in Tanjung Rejo Village, Kec. Percut Sei Tuan, Kab. Deli Serdang, North Sumatra Province. This program is supported by partners, government and youth organizations in Tanjung Rejo Village. The program is the first of three years planned program. It is hoped that during the three years of the program running, the Open University of UPBJJ Medan will be able to turn Tanjung Rejo Village into a Smart Village with the criteria that the village community is aware of the importance of education for life, for family welfare, for the progress of the village, nation and state; rural communities will improve their education up to university; villager love to read; the youth villagers have a wide range of skills; teachers in the village have good teaching skills; villager officials have professional capabilities in administering village government administration, managing village finances, and processing village statistical data. Thus, it is hoped that the development of human resources in Tanjung Rejo Village will improve in the future.The first year programs in 2022 that had been implemented included (1) activities to equalize public perceptions to increase awareness of rural communities on the importance of early education and reading culture and to increase motivation for higher education for village youth; (2) training activities to analyze learning videos in the UT Online Smart Teacher Portal to improve teaching skills, critical thinking and creative skills for Kindergarten/PAUD, SD, SMP teachers in Tanjung Rejo Village; (3) compiling Environmental Education textbooks as a guide for teachers and parents in teaching students and children to read aloud environmental education books so that students and children love to read, perceive, love, and protect their living environment; (4) Instruct teachers and parents on how to read environmental education textbooks to students and children; (5) publish program activities in newspapers in North Sumatera.Keywords: educational motivation, environmental education, reading attentiveness, smart village,teachers tutoringABSTRAKProgram pengembangan model Kampung Cerdas untuk meningkatkan motivasi pendidikan masyarakat ini dilakukan di Desa Tanjung Rejo, Kec.Percut Sei Tuan, Kab. Deli Serdang, Provinsi Sumatera Utara. Program ini didukung oleh mitra, Pemerintahan Desa dan Karang Taruna Desa Tanjung Rejo. Program ini merupakan program tahun pertama dari tiga tahun yang direncanakan. Diharapkan selama tiga tahun program berjalan, Universitas Terbuka UPBJJ Medan akan mampu menjadikan Desa Tanjung Rejo menjadi Kampung Cerdas dengan kriteria masyarakat desa sadar akan pentingnya pendidikan bagi kehidupan, bagi kesejahteraan keluarga, bagi kemajuan desa, bangsa dan negara; masyarakat desa akan meningkatkan pendidikan hingga perguruan tinggi; masyarakat desa gemar membaca; pemuda desa memiliki berbagai keterampilan; guru di desa memiliki keterampilan mengajar yang baik; aparat desa memiliki kemampuan profesional dalam menyelenggarakan administrasi pemerintahan desa, pengelolaan keuangan desa, dan pengolahan data statistik desa. Dengan demikian, diharapkan pembangunan dan pengembangan SDM di Desa Tanjung Rejo akan meningkat di masa depan